Up and about! : 20 activities for primary school (Chennai : Orient Longman Ltd, 1994)
This resource book for teachers presents pleasant and effortless early learning activities aimed at promoting creativity among children and making the learning experience more pleasant. The innovative techniques presented here have been developed through experimentation in Sri Atmananda Memorial School, Kerala. Sections on Science, Mathematics, English and others have well-planned activities that guide teachers by explicitly stating the aims, duration, age groups, materials and preparation required.
Keywords: 20 activities for primary school